Hybrid high‐voltage direct current topology with line commutated converter and modular multilevel converter in series connection suitable for bulk power overhead line transmission. Issue 12 (1st October 2016) - Xu, Zheng; Wang, Shijia; Xiao, Huangqing
Abstract : In this study, a hybrid high‐voltage direct current (HVDC) topology with line commutated converter (LCC) and modular multilevel converter (MMC) in series‐connection is proposed, which is suitable for bulk power overhead line transmission. This topology is of operational flexibility in terms of active and reactive power controls, and is able to withstand ac and dc faults by the cooperative control of LCC and MMC. First, the operation principle and mathematical model are presented. Then, the control strategies for ac faults at rectifier and inverter side are discussed, which can prevent current cut‐off under ac fault at rectifier side as well as maintain part of active power if commutation failure of LCC occurs under ac fault at inverter side. In addition, the feasibility on dealing with dc fault is theoretically demonstrated by analysing the characteristic of MMC under blocking state. A detailed control strategy for dc fault is further proposed combined with a test system. Finally, the effectiveness of the control strategy for ac and dc faults is verified and further compared with LCC‐based HVDC topology through time‐domain simulation.